REGULATION OF FILTRATION CHARACTERISTICS OF HIGHLY WATERED TERRIGENOUS FORMATIONS USING COMPLEX CHEMICAL COMPOSITIONS BASED ON SURFACTANTS - Korolev, Maxim; Rogachev, Mikhail; Tananykhin, Dmitry (Journal of Applied Engineering Science, 2020)
A significant share of Russian oil fields has entered the final stage of development and is characterized by a drop in production. It comes true due to the depletion of active oil reserves, and, as a consequence, an increase in the proportion of residual oil trapped in areas which are not covered by flooding, and physically or chemically associated with the formation of oil. An additional factor is the increase in the water content of complex-structured terrigenous reservoirs and their high number of permeable intervals.Development of the considered productive formations is carried out, as a rule, with maintenance of reservoir pressure by means of "cold" flooding. Despite the development and relatively low cost, it has its limitations/restrictions. The main reasons why we are not able to achieve complete displacement of oil by "cold" water are the difference between the viscosity of oil and the displacing agent, their immiscibility and hydrophobization of reservoir rocks [14].All methods of enhanced oil recovery (EOR) used for highly watered oil fields with hard-to-recover reserves are aimed at additional recovery of residual oil and achieving the design oil recovery factor (ORF), by optimizing the flooding system and upgrading the flooding agents.The design ORF can be achieved by increasing the water flood displacement efficiency, by improving the washing capacity of water (displacement agent), or by increasing the sweep efficiency of the reservoir flooding.
Keywords: change in filtration flows; dynamic modeling; methods of enhanced oil recovery; terrigenous formations; heterogeneity; emulsions